Corporate rights of the participant of the economic community: problems of legal regulation - Shevchuk, Oksana; Bober, Sofiia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to the study of the peculiarities of legal regulation and the problems of realization of corporate rights of participants of economic societies in Ukraine